Programmed hypocoagulation in combination with reinfusion of one’s own cell-like mass in complex treatment of children’s appendicular peritonits - A. L. Solnyshco; V. A. Shalygin; D. A. Boldyshev; R. V. Bocharov (Бюллетень сибирской медицины)
Patients with an appendicular peritonitis were studied with the disfunctions of a hemostasis and modular conditions of a blood. The experiments were carryed-out with the help of an analyzer of the reological properties ARP-01 «Mednord». 22 children had been examined. The scheme of the developing hypocoagualation was developed. The positive effect of combination of controlled gipocoagulation and antibiotic therapy is marked with the help of cell-like mass inkubation method.